Eugenia dysenterica DC: Actividad antioxidante, Perfil de ácidos grasos y determinación de tocoferoles - Jorge, Neuza [UNESP]; Luzia, Débora Maria Moreno [UNESP]; Bertanha, Bruna Jorge (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2010)
This work aimed to characterize the proximate composition, antioxidant activity and fatty acids profile and tocopherol composition of the oil from Eugenia dysenterica DC seeds. To obtain the extract, the dehydrated and triturated seeds were extracted with ethyl alcohol for 30 minutes, at a proportion of 1:3 of seeds:ethyl alcohol, under continuous agitation at room temperature. Afterwards, the mixture was filtered and the supernatant was dehydrated at 40°C in order to determine by direct weighing the dry matter yield of the extract. The cagaita seeds showed to be an important source of total carbohydrates, had relevant antioxidant activity and a high content of total phenolic compounds. In comparison to other oils and fats, cagaita seeds oil do not constitutes a good source of tocopherols.
Eugenia dysenterica DC: Antioxidant activity, Fatty acids profile and tocopherols determination
Keywords: Antioxidant activity; DPPH; Phenolic compounds; Seeds; Eugenia dysenterica